PRODUÇÃO E QUALIDADE NUTRICIONAL DA FORRAGEM E DA SILAGEM PRÉ-SECADA DE DIFERENTES CEREAIS DE INVERNO COLHIDOS EM ESTÁDIO DE PRÉ-FLORESCIMENTO - Horst, Egon Henrique (2016)
The use of preserved foods, such as pre-dried silage of winter cereals, are becoming a tool for intensive system maintenance. However, the quantity and quality of forage produced by winter cereals depends on several factors, which we point out the variability between species, genotypes of the same species and their adaptabilities to different environmental conditions. This study aims to measure the productivity of twelve cultivars from winter cereals harvested in preflourishing stadium in Guarapuava-PR region, and to evaluate the nutritional quality of forage and the resulting pre-dried silage. As experimental material we used black oat (Avena strigosa) cv. EMB 139 and cv. IAPAR 61; white oat (Avena sativa) cv. IPR and 126 hp. URS Taura; barley (Hordeum vulgare) cv. BRS Brau and cv. BRS Cauê; wheat (Triticum aestivum) cv. BRS Umbu and cv. BRS Tarumã; rye (Secale cereale) cv. Temprano and cv. BRS Serrano; and triticale (X Triticosecale) cv. IPR and 111 hp. BRS Saturn. Triticale cv. IPR 111 was the earliest producer of pre-dried in pre-flowering stage (94 days). The oat cv. IAPAR 61 and oat cv. IPR 126 were the most productive. Triticale cv. IPR 111 was shown as a high quality nutritional food as fodder, and kept these characteristics after preservation (21471 e 20684 kg GM ha-1). While the pre-dried silage barley cv. BRS Cauê showed the greatest potential for nutrient degradability (61.47% of TDN). In addition, it was noted that variations on the composition of the fiber and ruminal degradation kinetics between species and cultivars, however, all materials studied showed good degradability. It was observed similarity between the degradability results of forage and pre-dried silage, having the same trends. Barley cv. BRS Brau had the highest hemicellulose content in its composition (31.9%), however, the IPR 111 triticale was the treatment with the highest potential degradability, both as fodder as pre-dried silage.